William James, Gustav Fechner, and Early Psychophysics - Hawkins, Stephanie L. (Frontiers in Physiology, 2011)
American psychologist and philosopher William James devoted the entirety of his career to exploring the nature of volition, as expressed by such phenomena as will, attention, and belief. As part of that endeavor, James's unorthodox scientific pursuits, from his experiments with nitrous oxide and hallucinogenic drugs to his investigation of spiritualist mediums, represent his attempt to address the "hard problems" of consciousness for which his training in brain physiology and experimental psychology could not entirely account. As a student, James's reading in chemistry and physics had sparked his interest in the concepts of energy and force, terms that he later deployed in his writing about consciousness and in his arguments against philosophical monism and scientific materialism, as he developed his “radically empiricist” ideas privileging discontinuity and plurality. Despite James's long campaign against scientific materialism, he was, however, convinced of the existence of a naturalistic explanation for the more "wayward and fitful" aspects of mind, including transcendent experiences associated with hysteria, genius, and religious ecstasy. In this paper, I examine aspects of James's thought that are still important for contemporary debates in psychology and neuroscience: his "transmission theory" of consciousness, his ideas on the "knowing of things together," and, finally, the related concept of "the compounding of consciousness," which postulates the theoretical possibility for individual entities within a conscious system of thought to "know" the thoughts of others within the system. Taken together, these ideas suggest that James, in spite of, or perhaps because of, his forays into metaphysics, was working toward a naturalistic understanding of consciousness, what I will term a "distributive model," based on his understanding of consciousness as an "awareness" that interacts dynamically within, and in relation to, its environment.